Spiritual Quotient and Organizational Citizenship Behavior in Higher Education - Yuniarwati; Ardana, I Cenik; Dewi, Sofia Prima (International Journal of Psychosocial Rehabilitation, 2020)
This study aims to (1) test the measurement model (outer model) of Spiritual Quotient developed by Milliman et al. and the measurement model of Organizational Citizenship Behavior developed by Podsakoff et al., (2) examine the structural model (inner model) of Spiritual Quotient and Organizational Citizenship Behavior, and (3) test the hypothesis of the influence of Spiritual Quotient on Organizational Citizenship Behavior. The research sample was taken in a convenient manner from the population of lecturers of Tarumanagara University, Jakarta in 2018. Data were processed using Smart Partial Least Square. The results of this study indicate that: (1) Milliman et al.’s Spiritual Quotient measurement model and Podsakoff et al.’s Organizational Citizenship Behavior measurement model are valid and reliable after deleting several indicators that do not meet the requirements, (2) the relationship of Spiritual Quotient with Organizational Citizenship Behavior is positive but weak, and (3) the effect of Spiritual Quotient on Organizational Citizenship Behavior is quite significant at a 5% confidence level.